Application of Multi Criteria Supporting Elemination and Choice Translation Reality (ELECTRE) Decision in Determining Scholarship Recipients for Employee Children at PT. Nusira - Mesran Mesran; Afsah Rizki; Natalia Silalahi (STMIK Budi Darma, 2019)
During this time the determination of scholarship recipients for employees' children at PT. Nusira is not so good and is considered not so objective because it is still done by direct election and carried out manually so that it causes nepotism or prioritizes choosing employees who have high positions so that it is not so fair for ordinary employees. Due to the absence of a good system, causing problems to arise in terms of determining the receipt of scholarships for employees' children. Therefore, by using a decision support system based on Elimination and Choice Translation Reality (Electre). It is expected that decision-makers will be helped and reduce existing problems, especially in determining the acceptance of scholarships for employees' children.